2021
DOI: 10.1155/2021/4570388
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Fuel Cell: Recent Developments in Organic Substrate Use and Bacterial Electrode Interaction

Abstract: A new bioelectrochemical approach based on metabolic activities inoculated bacteria, and the microbial fuel cell (MFC) acts as biocatalysts for the natural conversion to energy of organic substrates. Among several factors, the organic substrate is the most critical challenge in MFC, which requires long-term stability. The utilization of unstable organic substrate directly affects the MFC performance, such as low energy generation. Similarly, the interaction and effect of the electrode with organic substrate ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 137 publications
0
29
0
Order By: Relevance
“…According to earlier literature, one of the causes for the voltage trend decreasing throughout operation is the use of organic substrate. The organic substrate must be sufficient to supply fuel for bacterial activities for an extended survival [ 43 , 44 ]. In the present study, both electrodes showed excellent performance because electrodes are used to transport the electrons.…”
Section: Resultsmentioning
confidence: 99%
“…According to earlier literature, one of the causes for the voltage trend decreasing throughout operation is the use of organic substrate. The organic substrate must be sufficient to supply fuel for bacterial activities for an extended survival [ 43 , 44 ]. In the present study, both electrodes showed excellent performance because electrodes are used to transport the electrons.…”
Section: Resultsmentioning
confidence: 99%
“…However, the external circuit decayed more rapidly to only about 0.04 V at about 10 h. The reason for the decay of the open-circuit potential and the external-circuit potential may be that after the consumption of the substrate glucose, the electron supply is insufficient, resulting in the decay of the open-circuit potential and a corresponding decay of the external circuit. However, the decay of the external circuit is more rapid due to the consumption of electrons [ 27 29 ]. The greater improvement in the electricity production performance of the modified strain compared to that of the original 5D strain may be due to the intracellular accumulation of more NADH after knocking out the gene related to lactate dehydrogenase.…”
Section: Resultsmentioning
confidence: 99%
“…Thermophotovoltaic [40] p-GaAs/ n-Ge cell /p-Ge/ Allowing greater absorbency of the light source, compact cell layers with band-gap energy-optimized 10.9 % Piezoelectric [41] KNN/Mn/KCT Material Along with enhanced densification. Lead-free content Elevated Curie temperature, Piezoelectric coefficient, and electromechanical coupling element 10,000𝑚𝑊/𝑐𝑚 3 Microbial fuel cell [42] Surface field combinations of anode-to-cathode Smooth electrons with reduced internal resistance flow from anode to cathode 6.86𝑊/𝑚 2 At 2.62 𝑚𝐴/𝑐𝑚 2…”
Section: -Future Potential Of Energy Harvesting Technology To Supply Power To Standalone Iot Devicesmentioning
confidence: 99%